Visualization Network Analysis of Studies on Agricultural Drainage Water Treatment - Wang, Chaoqun (2023)
Excessive chemical substances in agricultural drainage water have serious adverse effects on the ecological environment of the watershed into which they are discharged. Therefore, it has attracted widespread attention from scholars worldwide. In this paper, 282 scientific articles related to agricultural drainage water treatment are selected from the Web of Science Core Collection database, and CiteSpace was used to visualize and analyze the knowledge map of this field. The most productive authors, institutions, and countries in agricultural drainage water research are graphically presented in this paper. Developing countries are becoming the core force in this realm of inquiry. In addition, this paper explains the changes in research topics in this field over time and reveals current research hotspots, including “desalination”, “denitrification”, and “phosphorus removal”. Future research endeavors in using bioreactors and agricultural drainage water ditches for treating agricultural drainage water are implied to become a research focus in this field. This paper also emphasizes that future environmental protection research should increase case studies in developing countries and develop corresponding solutions based on the actual situation of agriculture in rural areas of developing countries.